Agresivitas Remaja Kebayoran Lama Selatan Dalam Tawuran Antar Geng Melalui Prespektif Differential Association Theory - Muhammad Ikhsan Alfaridzi; Nadia Utami Larasati (Anomie, 2023)
The study investigated the presence of criminal problems caused by a variety of elements such asgroup solidarity, the social environment, family, and the economy. The study attempts to explainwhat variables encourage students to bid and what motivates a student to act as a result of socialmedia. The researchers interviewed four sources for this study: two kids from separate gangs, oneWartul gang alumni, and the Head of the Criminal Resort Unit, Polsek Kebayoran Lama. Theresearchers expected to get a picture of what happened to students who performed the offer actiondue to the presence of paroses imitating and learning from social media from its predecessor inthe Southern Jakarta Boengkem gang by using a qualitative research approach with a descriptivetype. Factors that contribute to the occurrence of a conflict between school gangs or bands are classified as 2 (two), one of which is an internal element relating to adolescents' emotional well- being. External elements such as the home environment, the school environment, and the surrounding environment are also considered. Teen aggression, offer, differential association theory are all keywords.